Enhanced thermal conductivity of epoxy/three-dimensional carbon hybrid filler composites for effective heat dissipation. Issue 58 (25th June 2015) - Park, Ji Sun; An, You Jin; Shin, Kwonwoo; Han, Jong Hun; Lee, Churl Seung
<x xml:space="preserve">Abstract</x> A three-dimensional carbon-based heat-dissipating material was designed to improve the thermal conductivity of polymer composites in both the xy- and z-directions.